The Use of Management Tools and Added Value in Slovenian Disabled Enterprises - Šoster Gorazd; Markič Mirko (Naše gospodarstvo/Our economy, 2013)
The purpose of the survey is to establish the state in planning and use of manage- ment tools in disabled enterprises operating in the Republic of Slovenia. We investigated if a statistically significant correlation exists between planning and using the management tools and the added value. We found that disabled enterprises that are planning and implementing management tools do not achieve higher added value. The management tool connected to the increase of the added value is the EFQM. The essential advantages of using the management tools are: improved transparency of the processes, better quality of products, greater customer satisfaction, and improved reputation of the company. The conclusions of the survey will be useful to those who strive for continuous improvement of business efficiency.